2009
DOI: 10.1007/s10549-009-0478-y
|View full text |Cite
|
Sign up to set email alerts
|

Changing pattern of age-specific breast cancer incidence in the Swiss canton of Geneva

Abstract: Hormone replacement therapy (HRT) use declined sharply after mid-2002, when the Women's Health Initiative trial reported an association between breast cancer occurrence and HRT. Hypothesized mechanism behind this association is that HRT promotes growth of pre-existing small tumors, leading to earlier tumor detection. We evaluated the impact of the sudden decline in HRT use on age distribution of breast cancer in Geneva. We included all incident breast cancer cases recorded from 1975 to 2006 at the Geneva cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
0
16
0
2
Order By: Relevance
“…In an analysis based on data from nine US cancer registries, Ravdin et al reported a 7% overall decrease in incidence between 2002 and 2003 in women older than 50 years of age and particularly for estrogen receptor positive tumors [1]. Subsequent studies from the US, Canada, Australia, France, Switzerland, Germany, Great Britain, Belgium, and the Nordic countries have also reported reductions in breast cancer incidence [2][3][4][5][6][7][8][9][10][11][12][13][14]. These changes have been hypothesized to be a result of a dramatic decline in the use of hormone replacement therapy (HRT) following the 2002 release of the report from the Women's Health Initiative (WHI) hormone trial [15].…”
Section: Introductionmentioning
confidence: 99%
“…In an analysis based on data from nine US cancer registries, Ravdin et al reported a 7% overall decrease in incidence between 2002 and 2003 in women older than 50 years of age and particularly for estrogen receptor positive tumors [1]. Subsequent studies from the US, Canada, Australia, France, Switzerland, Germany, Great Britain, Belgium, and the Nordic countries have also reported reductions in breast cancer incidence [2][3][4][5][6][7][8][9][10][11][12][13][14]. These changes have been hypothesized to be a result of a dramatic decline in the use of hormone replacement therapy (HRT) following the 2002 release of the report from the Women's Health Initiative (WHI) hormone trial [15].…”
Section: Introductionmentioning
confidence: 99%
“…From 2000 to 2006, among women aged 50–69 years the rates hardly changed; in the ≥70-year age group the rates were unstable, presumably because of limited numbers. Other findings reported from Switzerland46 47 were based on small numbers, and the rates were unstable.…”
Section: External Consistencymentioning
confidence: 89%
“…It is likely that for chronic diseases, unexpected period effects -when statistically significant -have little impact on the estimation of age and cohort effects and is often ignored as it is the source of relatively small variations (Remontet et al, 2003). However, as shown in recent studies on breast cancer incidence (Ravdin et al, 2007;Bouchardy et al, 2010), sudden changes in chronic disease incidence can be observed over a short period of time. In the situation where a period effect is expected due to simultaneous changes in the exposure of all cohorts or variations in disease surveillance, it is possible that the period effect is overestimated if such changes lead to sudden variations in disease incidence within a short period of time, potentially resulting in a poor estimate of the trend and/or incidence of the disease and in inadequate public health decisions.…”
Section: Estimates Of the Birth Cohort Prevalencementioning
confidence: 93%